Non-volatile tuning of narrowband guided-mode resonance with strong absorption modulation - Peiyu Sun; Shichen Cao; Jiachen Yu; Qiqige Wulan; Li Xing; Yue Liu; Zhijun Liu (AIP Advances)
Dynamic resonance tuning enables the development of active optical devices with reconfigurable functionalities, which are of importance for many technological applications. In this work, we demonstrate non-volatile tuning of a narrowband guided-mode resonance (GMR) with strong light absorption modulation. By fabricating a waveguide grating integrated with a phase-change Ge2Sb2Te5 (GST) thin film, a tunable GMR is measured in the mid-infrared region. The GMR is shifted from 10.24 to 10.99 μm with a wavelength tuning range of 0.75 μm when the GST film is changed from the amorphous state to the crystalline phase. At the resonance wavelength of 10.24 μm, a modulation depth of 94% in absorption is measured. Continuous tuning of the GMR is also obtained by controlling the intermediate phases of the GST film. These results manifest the great potential of active GMRs, which are suitable for applications in infrared modulation, thermal emissivity control, camouflaging, etc.